Feminist perspectives on sustainable development - Harcourt, Wendy 1959-; Society for International Development (London, UK Zed Books Ltd, in association with Society for International Development, Rome, 1994)
This collection captures the vitality and urgency of feminists' responses to the environment and development debate. The authors - researchers, activists and policy-makers from North and South - offer new ways of challenging the present dominating knowledge-systems and development institutions, and discuss the difficulties women face on the margins of the development process. Contributions on resource management, power, knowledge production, culture, development institutions and politics, health and economics, show how gender relations are not simply a footnote to our understanding of history and societies, but must be central to the development discourse. In so doing, they suggest that diversity itself is necessary to the creation of new paradigms of development that are built upon gender equity, secure livelihoods, ecological sustainability and political participation.
Negotiating positions in the sustainable development debate : situating the feminist perspective / Wendy Harcourt -- Feminist orientalism and development / Fredeique Apffel-Marglin, Suzanne L. Simon -- Mining development in the Pacific : are we sustaining the unsustainable? / 'Atu Emberson-Bain -- The logic of economics vs. the dynamics of culture : daring to (re)invent the common future / Raff Carmen -- Beyond GNP / Hazel Henderson -- The south wind : towards new cosmologies / Corinne Kumar D'Souza -- Between terraforming and fortune-telling / Nina Lykke, Mette Bryld -- Sustainable development through women's groups : a cultural approach to sustainable development / Corinne Wacker -- Women and the politics of sustainable development / Sabine Hausler -- Interbeing and the Ì' habit : an experiment in environmental literacy / Julia Martin -- The politics of research on gender, environment and development / Willy Douma, Heleen van den Hombergh, Ange Wieberdink -- Feminism and political change : women's peace movements / Frances Connelly -- Biodiversity and gender issues : recognizing common ground / Janet N. Abramovitz -- Women, poverty and population : issues for the concerned environmentalist / Gita Sen -- Finiteness, infinity and responsibility : the population-environment debate / Franck Amalric -- Consumption and fertility / Helga Moss.
Photocopy.
Includes bibliographical references and index.
Keywords: Feminist theory; Sustainable development; Women in development